2007
DOI: 10.1111/j.1742-1241.2007.01567.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of oxycodone for management of acute pain episodes in chronic neck pain patients

Abstract: Oxycondone controlled release could be an important optional drug for the management of refractory and frequent acute episodes of chronic neck pain in patients who failed to respond to non-opioid conservative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
0
23
1
1
Order By: Relevance
“…One report showed that short-term administration of 5 to 10 mg oxycodone was effective in the control of acute neck pain [17]. It was also reported that intravenous injection of 0.3 mg/kg morphine in patients with chronic whiplash injury decreased the pain by 50% or more [18].…”
Section: Early Opioid Treatmentmentioning
confidence: 99%
“…One report showed that short-term administration of 5 to 10 mg oxycodone was effective in the control of acute neck pain [17]. It was also reported that intravenous injection of 0.3 mg/kg morphine in patients with chronic whiplash injury decreased the pain by 50% or more [18].…”
Section: Early Opioid Treatmentmentioning
confidence: 99%
“…Oncologic resections of the head and neck are of particular interest, since postoperative pain suffers interference from movements of the neck and swallowing, which can exacerbate the pain and result in failure of the analgesics treatment. Controlled-release oxycodone may be an important drug option for the treatment of acute refractory and frequent episodes of chronic neck pain in patients with response failure to conservative non-opioid treatment 10 . The recent interest for oxycodone is based on its pharmacokinetic and pharmacodynamic properties, especially on the central nervous system.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…In these conditions, central analgesics may be more appropriate, since they target the opioidergic system and the descending inhibitory pathways 10. The efficacy of opioids in neck pain and/or cervical radiculopathy has been poorly investigated to date,2527 whereas there is evidence supporting their use in low-back pain (LBP) 28…”
Section: Introductionmentioning
confidence: 99%